2002
DOI: 10.1364/ao.41.004722
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic technique for noninvasive monitoring of blood oxygenation: a feasibility study

Abstract: Replacement of invasive monitoring of cerebral venous oxygenation with noninvasive techniques offers great promise in the management of life-threatening neurologic illnesses including traumatic brain injury. We developed and built an optoacoustic system to noninvasively monitor cerebral venous oxygenation; the system includes a nanosecond Nd:YAG laser and a specially designed optoacoustic probe. We tested the system in vitro in sheep blood with experimentally varied oxygenation. Our results demonstrated that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(137 citation statements)
references
References 8 publications
1
133
0
3
Order By: Relevance
“…Savateeva et al 65 used a broadband detector (∼40 MHz) to measure the exponential slope of the PA signal in order to estimate the attenuation coefficient and showed that it varied linearly with the level of oxygen saturation at 532, 757, and 1064 nm wavelengths. Esenaliev et al 66 showed a similar result at 1064 nm with a lower bandwidth transducer. However, none of these authors provided estimates of absolute sO 2 .…”
Section: Cuvette Measurementsmentioning
confidence: 74%
“…Savateeva et al 65 used a broadband detector (∼40 MHz) to measure the exponential slope of the PA signal in order to estimate the attenuation coefficient and showed that it varied linearly with the level of oxygen saturation at 532, 757, and 1064 nm wavelengths. Esenaliev et al 66 showed a similar result at 1064 nm with a lower bandwidth transducer. However, none of these authors provided estimates of absolute sO 2 .…”
Section: Cuvette Measurementsmentioning
confidence: 74%
“…The main applications of the photoacoustic (PA) method are in the field of visualisation of strongly absorbing objects, such as blood vessels [263][264][265] and tumours [266]. This method can be also used for imaging of subcutaneous structures [267] and measuring the blood oxygenation [268]. The quality of the PA signal depends upon the penetration depth of the optical signal and the damping of the acoustic signal.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…PAT presents a hybrid imaging technique that combines the advantages of optical (high contrast) and ultrasound imaging (high resolution). It has proven great potential for important medical applications including cancer diagnostics [16,21] and imaging of vasculature [7,15].…”
Section: Introductionmentioning
confidence: 99%